Effect of Levothyroxine on the Some Biological Variables in Women with Hypothyroidism - Ali_Samarrai, Nuha Ali Hadi; Ali, Zainb Hussain (American Journal of Biomedicine and Pharmacy, 2025)
A recently discovered lipolytic adipokine called zinc-α2-glycoprotein (ZAG) has been linked to the control of lipid and glucose metabolism in a variety of metabolic diseases. The present study aimed to evaluated level of ZAG, malondialdehyde MDA, iron, lipid profile, thyroid stimulating hormones TSH, thyroxine T4, and triiodothyronine T3 in hypothyroidism patients after and before treatment. The cross sectional study investigated 90 women (60 patients newly diagnosed with hypothyroidism and 30 controls), their ages between (16- >60) years. All women with hypothyroidism diagnosed before and after treatment with levothyroxine for 3 months. The patients were referred to private clinics in Samarra from September 2024 to December 2025. This study showed decrease ZAG and iron level in hypothyroidism women before treatment, while increase after treatment as compared with control, ZAG value were (98.68±8.30, 110.96±7.55, 159.06±19.11) μg/ml respectively and iron value were (84.74± 8.04, 109.63± 13.95, 159.06±19.11) g/dL, at p-value P<0.001. MDA levels were significantly higher pre-treatment and elevated post-treatment compared to the control group(5.46±0.60, 2.59±0.44, 1.83±0.76) nmol\ml respectively, p-value <0.001. The lipid profile comprises total cholesterol, triglycerides, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). A statistically significant difference (P-Value = 0.01) was noted, Value of Cholesterol were (223.10± 11.72, 203.77± 9.09, 175.53± 9.44) mg/dl, while (132.03±36.58, 121.05± 4.25, 106.40± 8.93) mg/dl in triacylglycerol, (152.87±13.79, 128.57±10.41, 106.84±10.46 ) mg/dl in LDL, (35.51±1.90, 50.55±3.32, 47.93±2.80 )mg/dl in HDL. Serum ZAG , iron, HDL, T3, and T4, decreased before treatment while treatment with levothyroxine for period 3 months improve level of these parameters. Furthermore increase TSH , MDA, total cholesterol, triacylglycerol, LDL, levels in hypothyroidism patients and with treatment decrease it.